Effect of structure in ionised albumin based nanoparticle: Characterisation, Emodin interaction, and in vitro cytotoxicity - Siri, Macarena (2019)
A γ–irradiated bovine albumin serum-based nanoparticle was characterised structurally, and functionally. The nanoparticle was characterised by A.F.M, D.L.S, zeta potential, T.E.M., gelelectrophoresis, and spectroscopy. We studied the stability of the nanoparticle at different pH values and against time, by fluorescence spectroscopy following the changes in the tryptophan environment in the nanoparticle. The nanoparticle was also functionalized with Folic Acid, its function as a nanovehicle was evaluated through its interaction with the hydrophobic drug Emodin. The binding and kinetic properties of the obtained complex were evaluated by biophysical methods as well as its toxicity in tumour cells. According to its biophysics, the nanoparticle is a spherical nanosized vehicle with a hydrodynamic diameter of 70 nm. Data obtained describe the nanoparticle as nontoxic for cancer cell lines. When combined with Emodin, the nanoparticle proved to be more active on MCF-7 cancer cell lines than the nanoparticle without Emodin. Significantly, the albumin aggregate preserves the main activity-function of albumin and improved characteristics as an excellent carrier of molecules. More than carrier properties, the nanoparticle alone induced an immune response in macrophages which may be advantageous in vaccine and cancer therapy formulation.